Passively mode-locked ultrashort pulsed fiber laser incorporating multi-layered graphene nanoplatelet saturable absorber - Lau, K. Y.; Zainol Abidin, N. H.; Abu Bakar, M. H.; Latif, A. A.; Muhammad, F. D.; Huang, N. M.; Omar, M. F.; Mahdi, M. A. (Institute of Physics Publishing, 2018)
In this paper, a passive mode-locked erbium-doped fiber laser(EDFL)incorporating graphene nanoplatelet(GNP)powder-based saturable absorber(SA)with short pulse duration in femtosecond range is demonstrated. A good synthesis of GNP can be simply produced via a combination of hermal,chemical, and mechanical exfoliation of expandable graphite. The GNP-SA is fabricated by mechanically imprinting the powder onto the tip of a single mode fiber ferrule. The characterization of SA is done via focus ion beam scanning electron microscope, energy dispersive X-ray spectroscopy,as well as Raman spectroscopy. The fabricated GNP-SA has 1.8 % modulation depth and C-band transmission loss of less than 1.8 dB. The ring-configuration EDFL integrated with GNP-SA yields amode-locking threshold of 22.6 mW pump power. Net anomalous dispersion of the laser cavity is validated by the observation of Kelly’s sideband in the optical spectrum. At maximum pump power of115.8 mW, the mode-locked EDFL has a pulse repetition rate of 13.11 MHz, sech2 profile fitted pulse duration of 694 fs, peak-to-pedestal extinction ratio of 58.2 dB, average output power of 6.7 mW, and pulse energy of 507.2 pJ. Our proposed GNP-SA is feasible as a mode-locker for ultrashort pulsed fiber laser with advantage in terms of simple synthesis and fabrication technique.